Tuning the coordination behavior of an unexplored asymmetric multidentate ligand for developing diverse heterometallic architectures with luminescent and magnetic properties. Issue 4 (24th December 2020) - Song, Xue-Qin; Xia, Xue-Li; Song, Fu-Qiang; Liu, Guo-Hua; Wang, Li
Abstract : Three types of heterometallic species including metal clusters and a metal macrocycle have been developed by tuning the coordination behavior of a new asymmetric ligand with metal cations and anions. Abstract : Recently, by tuning the coordination behavior of a new asymmetric multidentate ligand, H 3 L, containing two nitrogen and six oxygen donors by both metal centres and anions, H 3 L = 1-(2-hydroxy-3-methoxy-benzamido)-2-(2-hydroxy-3-methoxy-benzylideneamino)-2-hydroxy propane, three types of heterometallic compounds with the chemical composition of [Zn8 Ln2 L2 (OH)4 (OAc)12 ]· x CH3 OH· y CH3 CN· z H2 O (Zn 8 Ln 2, where Ln = Nd, Tb, Dy and Er), [Ni3 Tb2 (HL)2 (OH)4 (OAc)6 ]·3CH3 CN·H2 O (Ni 3 Tb 2 ), and [Ni2 Tb2 (HL)2 (OAc)4 (NO3 )2 (H2 O)2 ]·4CH3 CN·3H2 O (Ni 2 Tb 2 ) were developed. Structural analysis revealed that four ellipsoidal decanuclear Zn II –Ln III clusters resulted from the assembly of H 3 L with Zn(OAc)2 ·2H2 O and Ln(OAc)3 ·6H2 O. Replacement of Zn(OAc)2 ·2H2 O with Ni(OAc)2 ·4H2 O rendered a butterfly pentanuclear Ni II –Ln III cluster, and upon further using Tb(NO3 )3 ·6H2 O to replace Tb(OAc)3 ·6H2 O, a tetranuclear Ni II –Ln III metallocycle was obtained. The luminescence studies on these compounds indicated that the Zn II -containing chromophore is a good antenna for sensitizing the characteristic emission of Ln 3+ effectively from the visible to near-infrared region as a result of its energy match, perfect shielding and less concentration quenching compared to its Ni II analogues, where the d → d transitions characteristic of Ni 2+ were observed in the excitation spectra when irradiated. Notably, weak emission bands characteristic of Tb 3+ were observed in the spectrum of Ni 2 Tb 2 but not in that of Ni 3 Tb 2 when excited by the d→d transition, which may be attributed to the difference in crystal field. Furthermore, the magnetic susceptibility studies indicate that the magnetic exchange for the Tb III ions in Zn 8 Tb 2, Ni 3 Tb 2 and Ni 2 Tb 2 is ferromagnetic, whereas that for the Dy III ions in Zn 8 Dy 2 is antiferromagnetic. Our results are of great significance for the rational design and synthesis of novel heterometallic supramolecular structures with interesting luminescence and magnetic properties.